Life creatures of the deep, plants and primates (BBC Worldwide Ltd. Program, 2010)
Creatures of the deep: Marine invertebrates are some of the most bizarre and beautiful animals on the planet, and thrive in the toughest parts of the oceans. Divers swim into a shoal of predatory Humboldt squid as they emerge from the ocean depths to hunt in packs. When cuttlefish gather to mate, their bodies flash in stroboscopic colours. Time-lapse photography reveals thousand of starfish gathering under the Arctic ice to devour a seal carcass. A giant octopus commit suicide for her young. A camera follows her into a cave which walls up, then she protects her eggs until she starves. The greatest living structures on earth, coral reefs, are created by tiny animals in some of the world's most inhospitable waters.